2009
DOI: 10.1158/0008-5472.can-08-4554
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gene Expression Profiles of Microdissected Cell Populations Indicates that Testicular Carcinoma In situ Is an Arrested Gonocyte

Abstract: Testicular germ cell cancers in young adult men derive from a precursor lesion called carcinoma in situ (CIS) of the testis. CIS cells were suggested to arise from primordial germ cells or gonocytes. However, direct studies on purified samples of CIS cells are lacking. To overcome this problem, we performed laser microdissection of CIS cells. Highly enriched cell populations were obtained and subjected to gene expression analysis. The expression profile of CIS cells was compared with microdissected gonocytes, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
132
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(141 citation statements)
references
References 47 publications
8
132
1
Order By: Relevance
“…Once the adult hypothalamus-testis-axis regulation is established, variations in either KITLG or AR may have only weak effect, if any, whereas the same polymorphism may exert stronger influence in the fetal period, when the initial step of the neoplastic transformation of germ cells takes place, which is hypothesized to be an arrest of gonocyte maturation . A recent global gene expression profiling study confirmed this long standing hypothesis that the CIS cells is a transformed gonocyte that failed to differentiate, most likely due to the improper hormonal function of the fetal somatic cells (21).…”
Section: Discussionmentioning
confidence: 76%
“…Once the adult hypothalamus-testis-axis regulation is established, variations in either KITLG or AR may have only weak effect, if any, whereas the same polymorphism may exert stronger influence in the fetal period, when the initial step of the neoplastic transformation of germ cells takes place, which is hypothesized to be an arrest of gonocyte maturation . A recent global gene expression profiling study confirmed this long standing hypothesis that the CIS cells is a transformed gonocyte that failed to differentiate, most likely due to the improper hormonal function of the fetal somatic cells (21).…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, our data support the common hypothesis of a different cell origin concerning spermatocytic seminoma and classic seminoma. 1,35 Although intratubular germ cell neoplasia unclassified is considered to be derived from developmentally arrested gonocytes, 2,[36][37][38] there is some controversy about the progenitor 39 Previous studies suspected primary spermatocytes 40 or spermatogonia 35,41 as progenitor cells. In our study, we found a strong expression of cancer testis antigens in spermatogonia and in spermatocytic seminoma, which is consistent with an origin of spermatocytic seminoma from spermatogonia, too.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies focused on pluripotency genes that were also retained in carcinoma in situ and TGCTs. Typical examples are the transcription factors NANOG, OCT4, TFAP2C (AP2g), and the miRNA-binding protein LIN28A, which are expressed not only in rodent and human fetal PGCs and gonocytes (Culty 2009, Weber et al 2010, but also in testicular tumors (Hoei-Hansen et al 2005, Rajpert-De Meyts 2006, Sonne et al 2009, Gillis et al 2011, Aeckerle et al 2012. In mouse and human ESCs, both NANOG and OCT4 were found to belong to a protein network regulating cell pluripotency, which included also Wnt and its downstream target b-catenin (AbuRemaileh et al 2010, Marucci et al 2014.…”
Section: Insights From Non-rodent Speciesmentioning
confidence: 99%
“…For example, it has been recently shown that the constitutive activation of the Notch pathway in fetal Sertoli cells led to premature changes in the behavior of fetal gonocyte, including premature exit from quiescence, migration, and differentiation, resulting in the loss of germ cells before birth . Interestingly, based on morphological and gene expression similarities, it has been suggested that improper gonocyte differentiation could lead to the formation of carcinoma in situ, the precursor pathology to testicular germ cell tumors (TGCTs; Skakkebaek et al 1987, Sonne et al 2009. Notably, the incidence of TGCTs has steadily been increasing over the past decades, for reasons that remain unknown (Huyghe et al 2003).…”
Section: Introductionmentioning
confidence: 99%